PUBLIC INTEREST IN GOLD INVESTMENT AT THE ANDI PETARRANI BRANCH OF SYARIAH PAWNSHIP, MAKASSAR CITY FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Andi Ulfha Nabhilah Soy (Az-Zahra Media Society, 2025)
This study aims to examine the public interest in gold investment at Pegadaian Syariah Andi Pangeran Pettarani Branch, Makassar City, and to review its practices from an Islamic economics perspective. The background of this research is the increasing public awareness of gold investment as a safe hedging instrument in accordance with sharia principles. This research employs a qualitative approach with a descriptive-analytical method. Primary data were obtained through in-depth interviews with five informants consisting of internal Pegadaian Syariah staff and customers, while secondary data were derived from literature and official documents. The results show that gold investment procedures at Pegadaian Syariah are simple, require affordable initial capital, and offer convenient transactions, both in cash and installments. Promotional strategies, such as direct education and digital media campaigns, have been effective in attracting public interest. From the perspective of Islamic economics, gold investment products at Pegadaian Syariah comply with sharia principles as they are free from riba, gharar, and maysir, and are implemented through murabahah and rahn contracts. The study concludes that public interest in gold investment is relatively high, influenced by factors such as ease of access, security, and adherence to Islamic economic principles